Mobile personal E-finance assistant - Suwandi, Adhikara Dimas (2013)
In the world today, there are varieties of challenges that will prevent people from achieving their financial goals. Rapid increase in price hikes for products and a staggering amount of debts have made saving money almost an impossible task. Despite that, most people still have no idea that they need to know their incomes and expenses to avoid any financial trouble in the future. Keeping track of expenses are necessary. In fact, it is a lot harder than keeping track of your incomes. For income, people can easily identify from their pay check. However, for expenditures, people tend to forget those small expenses. Those breakfast sets and meals will add up to your expenditure. In the end, people tend to underestimate their values which will lead to overspending.